Visions of political violence - Ruggiero, Vincenzo (Routledge, Taylor & Francis Group, 2020)
Introduction -- Systemic violence -- Institutional violence -- Crowds and group violence -- Conspiracy and the contemplation of crime -- Armed struggle and civil war -- Random killing and martyrdom -- Chaotic murder -- Belligerence as sexual violence -- Numinous terror -- Violence and social change -- Conclusion.